Implementasi Social Media Marketing Sebagai Upaya Meningkatkan Brand Awareness Pada UMKM Keripik Pisang “Dua Putra Putri” Di Desa Karangan - Devina Zulia Rahmatin; Nurul Azizah (Jurnal Pengabdian Kepada Masyarakat, 2023)
Many resources around the yard of the house are used by the people of Karangan Village to make MSME products, one of which is Mrs. Samilah who produces banana chips. The purpose of this community service is to empower MSME actors by creating work programs, mentoring activities and branding training, as well as social media marketing to increase brand awareness of MSME products "Dua Putra Putri" Banana Chips. The data collection method used is observation, interview, and discussion method while the data analysis method uses an inductive approach because this research is qualitative. The result of this service activity is that Mrs. Samilah as an MSME actor has gained knowledge related to branding strategies and social media marketing. Brand awareness of "Dua Putra Putri" Banana Chips products has also begun to increase, because social media marketing has been successfully carried out through Instagram and Facebook.